E-Government as A Tool to Increase Public Participation in Public Decision Making - Widiatmoko, Catur; Simarmata, Rajanner P.; Gunadi, Genta Arief; Amazihono, Memoranius; Watimena, Joko Susilo (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this research is to examine e-government as a tool to enhance public participation in decision-making. The researcher used qualitative research methods with a field research approach. Field research involves direct observation, interviews, or other data collection methods in the field, allowing the researcher to gain a deep understanding of the phenomenon under study. The research location for this study is the Jakarta Provincial Government. To gather information or collect data, two staff members of the Jakarta Provincial Government were interviewed. The findings of this study indicate that the use of e-government in the Jakarta Provincial Government has proven to enhance public participation in policy-making. E-government enables broader, more inclusive, targeted, and transparent participation. Public participation is facilitated through online platforms where people can easily access information and participate in discussions about proposed policies. In the context of the Jakarta Provincial Government, e-government has also helped improve the efficiency of governance and provide easier access to public services.